"We Don't Have the Right Words!": Idiomatic Violence, Embodied Inequalities, and Uneven Translations in Indian Law Enforcement. Issue 2 (2nd December 2020) - Fuchs, Sandhya
Abstract: This article interrogates the relationship among legal gatekeepers, embodied expressions of structural violence, and institutional patterns of translation in the mobilization of antidiscrimination legislation by examining a case registered under the 1989 Scheduled Castes/Scheduled Tribes Prevention of Atrocities Act in the Indian state of Rajasthan. The article proposes that law enforcement officials often utilize legal registers and legal aesthetics as defensive shields against the demands of historically marginalized groups, which interfere with their institutionalized moralities and wider loyalties to higher caste groups. Thereby they reinscribe the very structural inequalities antidiscrimination laws are intended to address. This process is often the result of a dual breakdown of translation. On the one hand, police officers often refuse to engage with the local linguistic idioms of marginalized communities in a way that makes their experiences legible to the law. On the other hand, survivors of discriminatory violence are themselves hesitant to make their suffering explicit due to trauma and fear of being publicly humiliated. Ultimately, this process can instill further feelings of inadequacy in victims of discrimination at the very moment they try to claim their rights. This case ultimately questions the ability of antidiscrimination legislation to effectively counteract the effects of structural inequality. [India, anti‐discrimination law, translation, caste, embodiment]